Relationship of CD146 expression to activation of circulating T cells: exploratory studies in healthy donors and patients with connective tissue diseases. (8th September 2013) - Hadjinicolaou, A. V.; Wu, L.; Fang, B.; Watson, P. A.; Hall, F. C.; Busch, R.
Summary The endothelial cell adhesion molecule, CD146, is expressed on ≈ 2% of normal circulating T cells, correlating with T cell activation, endothelial interactions and T helper type 17 (Th17) effector functions. In this study, we have characterized CD146 expression in circulating T cells from healthy controls and patients with stable, well‐controlled autoimmune connective tissue diseases (CTDs). In vitro, anti‐CD3/anti‐CD28 stimulation induced CD146 expression in both CD4 and CD8 T cells. In healthy controls and CTD patients, CD146 was associated with expression of recent and chronic activation markers (CD25+, OX‐40+, CD69+, CD27–) and was confined to CD45RO+/RA–/CD28+ populations within the CD4 subset. Except for CD69, these markers were not associated with CD146 in the CD8 subset. Surprisingly, most CTD patients exhibited no T cell hyperactivation ex vivo. In five of five patients with secondary Sjögren's syndrome circulating T cells appeared activated despite therapy, and CD146 up‐regulation, associated with activation markers, was observed both on CD4 and CD8 T cells. There was no association between CD146 and putative pro‐atherogenic T cell subsets. In conclusion, the relationship of CD146 expression to T cell activation differs between T cell subsets in healthy subjects and correlates with systemic hyperactivity, where present, in patients with CTDs, as exemplified by the patients with secondary Sjögren's syndrome in this study.